Information Literacy Instruction in Four Vietnamese University Libraries / Kim Chi Diep and Diane Nahl - Diep, Kim Chi; Nahl, Diane (2011)
This case study explored the perceptions of academic stakeholders about the development and delivery of information literacy (IL) programs in four universities, and identified elements necessary to establishing IL credit courses in Vietnamese higher education. The following research questions framed this study: 1) How do library administrators, instruction librarians, and faculty perceive the current implementation of information literacy instruction (ILI) programs for undergraduates studies in universities libraries in Vietnam? 2) What are the challenges to including IL as a credit course in the curriculum as perceived by library administrators, instruction librarians, and faculty? Respondents were purposefully recruited from four universities, including library administrators, instruction librarians, and faculty. Three online surveys distributed through Survey Monkey received 133 responses. Interview and focus group data collection included 23 face-to-face interviews and nine focus groups. Findings showed IL is considered the domain of librarians and has not influenced Vietnamese campus culture. IL activities at four university libraries take the form of lectures, workshops, and basic IL skills modules. Few ILI activities are subject discipline-related. Respondents reported challenges to an ILI credit course revolve around the lasting impact of teacher-centered instruction and rote learning, misperceptions about the effect of IL on student learning outcomes, degree of support of IL by academic stakeholders, degree of faculty-librarian collaboration, and scarcity of resources. Recommendations are given for academic librarians in Vietnam implementing ILI programs and considering developing IL credit courses.